Zeolitic imidazolate frameworks (ZIF-8) as a carrier in a topical ocular delivery system for the treatment of ocular diseases - Phillip A. Harding; James H. Westbay; Ethan Fletcher; Xin Fan; Morgan V. DiLeo (PLoS ONE, 2026)
Current systems for topical ocular drug delivery enable non-invasive administration of therapeutics to the eye but suffer from poor permeability and bioavailability, limiting therapeutic efficacy. Metal-organic frameworks are porous, crystalline materials that can serve as drug delivery systems and may improve these shortcomings. In this study, we explore the use of ZIF-8 as a representative metal-organic framework for topical ocular drug delivery. ZIF-8 particles were prepared via a simplified aqueous synthetic method and loaded with ovalbumin, a model molecule to simulate anti-angiogenic proteins that are used to treat retinal diseases. The physical properties of unloaded and loaded ZIF-8 were evaluated with a variety of spectroscopic, imaging, and desorption techniques that confirmed successful loading with ovalbumin (>46% loading capacity) without severe disruption to the structure of ZIF-8. In bulk solution, loaded ovalbumin is gradually released in a linear fashion for up to 60 days. Loaded ZIF-8 applied to chicken eggs or bovine eyes showed minimal to no levels of irritation, supporting our hypothesis that ZIF-8 can be safely applied to ocular tissue. When applied to ex vivo bovine eyes, loaded agents administered in ZIF-8 penetrate the sclera, suggesting ZIF-8 may enhance permeability to intraocular tissue. These results highlight the potential of ZIF-8 as a carrier in topical ocular delivery systems and provide a crucial foundation to evaluate their efficacy in topical ocular drug delivery using in vivo models.